The Relationship Between Treatment Adherence and Non-picked Up Medications in Community Pharmacies - Vu Phan Hoang Nguyen; Albert Wertheimer (University of Minnesota Libraries Publishing, 2016)
Medication adherence is one of the major factors that determine an outcome of a treatment. Despite the effort of healthcare providers to improve the adherence rate, it still remains a serious issue in our health care system today. Many patients do not take their medications as directed or just simply do not want to fill or refill their prescriptions. A small survey performed by pharmacy students at Temple School of Pharmacy showed that there is a significant number of patients did not pick up their medications. Cardiovascular medications are the most common non-picked up drugs. There are various reasons that patients use to justify for this non-adherence behavior. However, they are unaware that their actions create a tremendous negative effect not only on the treatment itself but also on the entire health care system. The consequences include expensive therapies, inaccurate research data, and poor treatment outcomes. Many solutions have been utilized to solve this problem, but it is still the major problem for healthcare providers to keep in mind when planning a drug regimen. Although many people believed that pharmacists are responsible for solving this problem, it should be a multidisciplinary effort of all healthcare providers to improve the medication adherence. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties.   Type: Student Project